Educational Psychology Aspect in Gaguritan I Jayaprana - I Wayan Mandra (Jurnal Penelitian Agama Hindu, 2020)
Gaguritan is a traditional literary work that has a fairly strict literary convention system. The work is formed by pupuh unit with a large number of syllables in each row, the number of row in each verse and the final sound in each row. Gaguritan as a form of traditional Balinese literature is a product of Indonesian literature, belongs to the poetry. Gaguritan is one type of traditional Balinese literature that still lives and develops in Balinese society. The literary work of the Gaguritan is still often read or sung in the pesantian activities. The results of this study concluded that the structure of Gaguritan I Jayaprana consists of: 1) The theme is woman faithfulness 2) The story line is conventional, occurring from several events caused by the cause and effect relationship 3) the characterization which consists of main character, I Jayaprana, secondary character Ni Layonsari, complementary characters namely, I Saunggaling, and Bendesa, The King 4) The moral value can be seen is the loyality of I Layonsari as a wife to her husband. The educational psychology aspect contained in the Gaguritan I Jayaprana can be seen in I Jayaprana. The character of I Jayaprana should be exemplary. In addition to learning diligently I Jayaprana also has high intelligence. Capable in reading and translating Kakawin.